Reliability Test Rig of the Motorized Spindle and Improvements on Its Ability for High-Speed and Long-Term Tests - Zheng Yang; Fei Chen; Wei Luo; Binbin Xu; Song Wang (Shock and Vibration)
To realize the accurate performance test under high-speed operation and the long-term stable reliability test of the motorized spindle, a reliability test rig (RTR) which can simulate the cutting force in the actual machining process is presented. Firstly, a reasonable prototype integrating dynamic force loading devices and torque loading devices is designed and established based on the load analysis of the spindle, and a complete and explicit control strategy of the reliability loading test is designed. Secondly, the effects of misalignment of the diaphragm coupling caused by assembling are analyzed, and experiments are conducted to test the axis orbit of the motorized spindle. The experimental results illustrate that the axis orbit can identify the occurrence of misalignment, which ensures timely adjustment of misalignment and the accurate performance test under high-speed operation. Lastly, a damper is added in the mechanical structure of the electrohydraulic servo loading system (EHSLS), and the comparison of Bode maps before and after optimization is analyzed by the Nyquist criterion. After the optimization, the gain and phase margin of the Bode diagram are 12.9 dB and 57.2°, respectively, which are both within the stable range and validate the improvements on the ability of long-term reliability tests of the motorized spindle. The presented RTR is able to simulate the actual cutting force and provides an efficient loading approach to guarantee the accuracy and stability of motorized spindle tests.